Child obesity prevention in primary health care: Investigating practice nurse roles, attitudes and current practices. Issue 4 (11th April 2013) - Robinson, Alison; Denney‐Wilson, Elizabeth; Laws, Rachel; Harris, Mark
<x xml:space="preserve">Abstract</x> Aim Overweight and obesity affects approximately 20% of Australian pre‐schoolers. The general practice nurse (PN) workforce has increased in recent years; however, little is known of PN capacity and potential to provide routine advice for the prevention of child obesity. This mixed methods pilot study aims to explore the current practices, attitudes, confidence and training needs of Australian PNs surrounding child obesity prevention in the general practice setting. Methods PNs from three Divisions of General Practice in New South Wales were invited to complete a questionnaire investigating PN roles, attitudes and practices in preventive care with a focus on child obesity. A total of 59 questionnaires were returned (response rate 22%). Semi‐structured qualitative interviews were also conducted with a subsample of PNs (n = 10). Results Questionnaire respondent demographics were similar to that of national PN data. PNs described preventive work as enjoyable despite some perceived barriers including lack of confidence. Number of years working in general practice did not appear to strongly influence nurses' perceived barriers. Seventy per cent of PNs were interested in being more involved in conducting child health checks in practice, and 85% expressed an interest in taking part in child obesity prevention training. Conclusions Findings from this pilot study suggest that PNs are interested in prevention of child obesity despite barriers to practice and low confidence levels. More research is needed to determine the effect of training on PN confidence and behaviours in providing routine healthy life‐style messages for the prevention of child obesity.